Leadership Strategy in Facing Organizational Change: Case study within the Kendari City Government - Adwi, Adwi; Zulkifar Mulyadi, Dwi; Dzulhaji Pratama Putra, Andika (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study explores effective leadership strategies in dealing with organizational change in the Kendari City government environment. By identifying the leadership approaches and practices adopted, this study seeks to provide insight into ways that can be applied to improve organizational adaptability and effectiveness in responding to the dynamics of change. This qualitative study collected data through in-depth interviews with 30 informants consisting of leaders in various departments of the Kendari City government. Data analysis was carried out using content analysis techniques to understand the perspectives, experiences, and leadership strategies used in managing change. This study uses a qualitative method with data collection through in-depth interviews with 30 informants consisting of leaders in various departments within the Kendari City Government. The data analysis technique used is content analysis, where data from interviews and documents are analyzed to identify key themes, patterns, and relationships between the concepts of leadership and change management. The research findings indicate that transformational and participatory leadership are key in dealing with organizational change. Successful leaders are those who are able to inspire, motivate, and involve team members in the change process. In addition, effective communication, consensus-based decision making, and employee empowerment are identified as practices that support the successful implementation of change strategies. Effective leadership strategies in dealing with organizational change require a combination of transformational and participative leadership styles. This study suggests the importance of leadership training that focuses on developing communication, decision-making, and empowerment skills for leaders in government environments. These findings are expected to contribute to the development of more adaptive and responsive leadership policies and practices to change in the public sector.